Development of antibiotic resistance in Gram negative bacilli: An eye opener - Ravinder Pal Singh; Sonali Jain; Parduman Singh; Nikunj Gupta (Medical Journal of Dr. D.Y. Patil University, 2014)
Context: Antibiotic resistance is a global problem. Organisms are showing resistance to not only the conventional antibiotics but also to the higher generation drugs. This enormous amount of resistance faced is a serious threat to mankind and this is further accentuated by the fact that the antibiotic pipeline is fast drying up. We are now left with only a handful of antibiotics to deal with all infections - serious or otherwise. The present paper highlights the current scenario of drug resistance especially in nosocomial settings. Aims and Objectives: To determine the distribution of bacterial pathogens causing nosocomial infections and their antibiogram, a surveillance data from January to December 2011 was collected in Mohan Dai Oswal Hospital. A total of 1800 samples were taken of which maximum samples were urine (766) followed by blood (428) and pus (216), and so on. Settings and Design: This observational study was conducted in the microbiology department of a multispeciality hospital during January-December 2011. Materials and Methods: A total of 1800 samples from different sources were included in the study like pus, blood, urine, sputum, etc., which were taken from patients admitted in the hospital for more than a week. Gram negative bacilli were isolated, identified, and subjected to antibiotic sensitivity test. Statistical Analysis Used: Descriptive statistics using percentages. Results: Out of the total 1800 samples included, maximum positivity was found in the pus samples (70%). Extended-spectrum beta-lactamase (ESBL) positivity was also maximum in the pus samples (90%). These ESBL positive organisms were further subjected to antibiotic sensitivity tests and huge amounts of resistance was noted to the conventional drugs including the higher end agents like Carbapenems. In light of this, newer drugs like Tigecycline, Colistin, and Polymyxin B were also tested. Barring Tigecycline, none showed favorable results. A noteworthy finding was the sensitivity of the urinary ESBL isolates to Nitrofurantoin. Conclusions: The situation is quite dangerous. The time is not far when we will be back in the dark ages of the preantibiotic era. The need of the hour is to be alert of the gravity of this situation and take necessary measures to halt its progress.